Building The Human Capital In The ‘Malakah’ Concept Of Ibn Khaldun : A Historical Study Based On His ‘Muqaddimah’ - Muhammad Uthman El-Muhammady, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2008)
The objective of this paper is a very modest one, namely to examine the thoughts of Ibn Khaldun on the important concept of ‘malakah’ or ‘habitus’ or ‘habit’. This will be done by concentrating on his ‘al-Muqaddimah’, letting his views shine through his actual statements from the work. This is to see how he understands the nature of this habitus, its attributes, significance and importance ,some of the factors leading to its enhancement, and factors which may hamper it. Finally its significance and relevance in relation to contemporary efforts in personality development and the enhancement of what is called ‘the human capital’, in the Islamic context, will be summarily discussed